Pemanfaatan Tanah, Kompos dan Arang Sekam untuk Pertumbuhan Tanaman Cabai - Nurul Mukhlishah; Faizah Mahi; Rosmiati Rosmiati; Herawaty Herawaty; Aswar Aswar (Publikasi Indonesia, 2022)
Chili plant is one type of vegetable that is widely cultivated by Indonesian farmers and has a variety of health benefits. However, sometimes the growth of chili plants is not optimal. One of the problems in maintaining the growth of chili plants is the lack of yields from the planted area. The cause of the lack of crop yields is that plants do not thrive, is the cause of chili plants not thriving, including the growth of weeds (weeds) around the location / center of the plant, the value of macro and micro nutrients in the soil is very lacking to maintain growth and development. plants, or soil contamination occurs which may be caused by waste such as detergents or excessive chemical fertilizers. With this, the authors provide counseling and training on making planting media by utilizing soil, compost, and husk charcoal and training in carrying out chili cultivation activities in polybags. The activity was carried out on April 9, 2022. The method applied was counseling and training with partners of the Lorong Cokonuri Farmer Group, Gunung Sari Village, Rappocini District, Makassar City. The results of the implementation showed that there was an increase in the knowledge and ability of farmers in making planting media. Furthermore, this is expected to have an impact on the growth of chili plants.